Cloud kingdom - Choo, Kessa Hui Yi (2019)
This report details our journey in producing our short documentary film Cloud Kingdom. It also aims to provide insights into our experience of filming the documentary. From initial conceptualisation, to pre-production research, until finally to post-production editing, the report discusses the challenges behind our filmmaking process, as well as the rationale behind the decisions that we have made.